Upaya Peningkatan Daya Saing Bisnis Perusahaan Melalui Manajemen Perubahan - Oriza Aditya; Alit Merthayasa (Syntax Idea)
The era of globalization creates changes and intense business competition. Companies that want to survive and succeed must be able to adapt to the changes that occur. The purpose of this research is to analyze efforts to improve the company's business competitiveness through change management. This research uses qualitative research methods. Data collection techniques were carried out with documentation studies of the secondary data type sourced from Google Schoolar. The data that has been collected is then analyzed through three stages, namely data reduction, data presentation and conclusion drawing. The results showed that efforts to improve the competitiveness of the company's business through change management were implemented in the form of restructuring. The form of restructuring can be pursued by reducing employees, changing the organizational structure, changing business processes, changing work culture, and changing information systems.